2020
DOI: 10.20402/ajbc.2020.0066
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Biological Activities of Diphylleia grayi Extract as a Natural Cosmetic Ingredient

Abstract: Purpose: In this study, we investigated the biological activities of Diphylleia grayi extract as a natural cosmetic ingredient. Methods: The antioxidant activities of Diphylleia grayi extract was measured through 2,2-diphenyl-1-(2,4,6-trinitrophenyl)hydrazinyl (DPPH), 2,2'-azino-bis-3-ethylbenzthiazoline-6-sulphonic acid (ABTS) scavenging assay and Fluorescence recovery after photobleaching (FRAP) assay. We further investigated whether Diphylleia grayi extract could reduce the intracellular reactive oxygen spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…또한, 병 원체 감염이나 상처 등의 식물 조직손상부를 보호하기 위해서 callus가 축적된 형태로 성장한 것이며 [25], 전형성능을 지니고 있어서 배양 환경과 배지 조성에 따라 성장 속도 조절, 대량 배 양 및 전체 식물체의 재생이 가능하다 [26]. 또한 접시꽃 callus 는 산화를 억제하는 작용이 뛰어나며 미백 효능을 가지고 있어 천연화장품 소재로써 활용 가치가 있다고 보고된 바가 있다 [27].…”
Section: 서 론unclassified
“…또한, 병 원체 감염이나 상처 등의 식물 조직손상부를 보호하기 위해서 callus가 축적된 형태로 성장한 것이며 [25], 전형성능을 지니고 있어서 배양 환경과 배지 조성에 따라 성장 속도 조절, 대량 배 양 및 전체 식물체의 재생이 가능하다 [26]. 또한 접시꽃 callus 는 산화를 억제하는 작용이 뛰어나며 미백 효능을 가지고 있어 천연화장품 소재로써 활용 가치가 있다고 보고된 바가 있다 [27].…”
Section: 서 론unclassified
“…It was reported that some species of genus Althea or Alcea (Malveceae) have different pharmacological activities. Althaea rosea, one of the most studied Alcea species, was reported to have cytotoxicity (Abdel-Salam et al, 2018;Al-Snafi, 2013), anticancer (Shahbipour et al, 2017), antimicrobial (Al-Snafi, 2013;Mert et al, 2010), anti-influenza (Sargin, 2021), antioxidant (Abdel-Salam et al, 2018;Dar et al, 2017;Kordalı et al, 2020;Lee et al, 2018), antihyperglycemia (Dar et al, 2017), hepatoprotective effects against paracetamol induced toxicity (Hussain et al, 2014), and curative / protective activity in rats with urolithiasis by decreasing the calcium oxalate deposits; which thought to be in relation with the anti-inflammatory and diuretic effects of mucilaginous and polysaccharides in the herb (Ahmadi et al, 2012). Antitussive, antimicrobial, and anti-inflammatory effects were mentioned for Althaea officinalis (Al-Snafi, 2013).…”
Section: Introductionmentioning
confidence: 99%